Impact of Ayurveda Based Ischemia Reversal Program (IRP) And Polyherbal Medication on Reduction of Resting Myocardial Ischemia with Speckle Tracking Global Longitudinal Strain Imaging in Type 2 Diabetes Mellitus Patients - Sane, MD, Rohit; Manohar, Pramod; Mandole, Rahul; Amin, Gurudatta; Ghadigaonkar, Pravin; Dongre, Snehal; Yanshwantrao, Prafull; Patil, Dinesh; Jadhav, Rahul (International Journal of Innovative Research in Medical Science, 2022)
Background: Type 2 Diabetes mellitus (T2DM) is a major public health problem with hyperglycaemia leading to ischemia and myocardial damage. Two-dimensional speckle-tracking global longitudinal strain (GLS) imaging is one of the non-invasive tools used for early onset detection of left ventricular systolic dysfunction (LVSD) which goes undetected in the traditionally used tools. The standard of care provided to diabetic patients leads to several adverse effects leading to non-compliance and higher incidences of mortality and morbidity. The current study aimed to evaluate the efficacy of alternative treatment (Ischemia Reversal Program and diet kit) in improving GLS score in T2DM patients. Methodology: This retrospective study was conducted from January 2020 to January 2021 in T2DM patients who attended the Cardiac Care Clinics, Mumbai. The patients underwent 14 sittings of IRP and calorie-controlled diet kit for 30 days. Change in GLS score from baseline formed the primary endpoint while the secondary endpoint were reduction in Body Mass Index (BMI), Abdominal girth (ABG), End diastolic volume (EDV)and dependency of modern medicines and outcome of 6 meter walk test (6MWT). Results: A total of 26 T2DM patients were enrolled with a mean age of 59 years. The GLS score (p=0.0004) and distance covered post 6MWT (p=0.03) showed a significant improvement post IRP treatment. There was a reduction in blood sugar levels and improvement in the cardiac parameters; the difference being not significant. Conclusion: IRP may be an effective and sustainable addition to standard treatment of T2DM and IHD though future large-scale studies are warranted.